A simple and effective 1, 2, 3-triazole based "turn-on" fluorescence sensor for the detection of anions. (29th October 2014) - Ghosh, Debanjana; Rhodes, Shannon; Hawkins, Karena; Winder, Domonique; Atkinson, Austin; Ming, Weihua; Padgett, Clifford; Orvis, Jeffrey; Aiken, Karelle; Landge, Shainaz
Abstract : 1, 2, 3-Triazole based chemosensor is synthesized using "Click chemistry" approach. Addition of fluoride ion "turn-on" the fluorescence response of probe. Abstract : A novel and effective 1, 2, 3-triazole based fluorescence chemosensor has been synthesized for the specific detection of anions in homogeneous medium. Notably, the molecule, synthesized in one step using "Click chemistry", is a simple 1, 4-diaryl-1, 2, 3-triazole, containing a phenol moiety. The probe displayed the strongest response to fluoride ion through the "turn-on" fluorescence sensing mechanism when screened for selectivity and sensitivity against a series of anions (F −, Cl −, Br −, I −, H2 PO4 −, ClO4 −, OAc −, BF4 − ). Fluorescence spectroscopy and Nuclear Magnetic Resonance Spectroscopy (NMR) studies substantiate 1 : 1 stoichiometry between the probe and fluoride anion. Kinetic studies and the single crystal X-ray spectroscopic evidence revealed the binding interaction occurs with the phenolic group and the anion.